Unmasking age : The significance of age for social research - Bytheway, Bill (Bristol, UK : Policy Press, 2011)
Unmasking Age critically examines various methods and discusses ways of uncovering the realities of age.
Title from publisher's bibliographic system (viewed on 07 Sep 2022).
Keywords: Age -- Social aspects; Age -- Social aspects -- Research; Social sciences -- Research -- Methodology